\(\dfrac{10}{7}\) . x = \(\dfrac{4}{7}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x=4/27-2/3=4/27-18/27=-14/27
b: =>3/4x-1/4x=1/6+7/3
=>1/2x=1/6+14/6=5/2
hay x=5
c: =>13/10x=7/2+5/2=6
=>x=13/10:6=13/60
d: (3x+2)(-2/5x-7)=0
=>3x+2=0 hoặc 2/5x+7=0
=>x=-2/3 hoặc x=-35/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a, bằng \(\dfrac{10}{7}\) nha em, sorry chị nhìn lộn 5 thành 3
a, \(x=\dfrac{-4}{7}:\dfrac{-2}{3}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b, \(\dfrac{2}{3}.x=\dfrac{3}{7}-\dfrac{5}{7}\)
\(\dfrac{2}{3}.x=\dfrac{-2}{7}\)
\(\Rightarrow x=\dfrac{-3}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x\) : \(\dfrac{13}{3}\) = -2,5
\(x\) = -2,5 . \(\dfrac{13}{3}\)
\(x\) = \(\dfrac{65}{6}\)
b,\(\dfrac{3}{5}\)\(x\) = \(\dfrac{1}{10}-\)\(\dfrac{1}{4}\)
\(\dfrac{3}{5}x\) = \(\dfrac{-3}{20}\)
\(x\) = \(\dfrac{-3}{20}\) : \(\dfrac{3}{5}\)
\(x\) = \(\dfrac{-1}{4}\)
c, \(\dfrac{25}{9}-\dfrac{12}{13}x=\dfrac{7}{9}\)
\(\dfrac{12}{13}x\)\(=\dfrac{25}{9}-\dfrac{7}{9}\)
\(\dfrac{12}{13}x=2\)
\(x=2:\dfrac{12}{13}\)
\(x=\dfrac{13}{6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x - 3)(6 - 2x) = 0
=> \(\left[{}\begin{matrix}2x-3=0\\6-2x=0\end{matrix}\right.=>\left[{}\begin{matrix}2x=3\\2x=6\end{matrix}\right.=>\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=3\end{matrix}\right.\)
b) \(5\dfrac{4}{7}:x=13=>\dfrac{39}{7}:x=13=>x=\dfrac{39}{7}:13=>x=\dfrac{3}{7}\)
c) \(2x-\dfrac{3}{7}=6\dfrac{2}{7}=>2x-\dfrac{3}{7}=\dfrac{44}{7}=>2x=\dfrac{47}{7}=>x=\dfrac{47}{14}\)
d) \(\dfrac{x}{5}+\dfrac{1}{2}=\dfrac{6}{10}=>\dfrac{x}{5}=\dfrac{6}{10}-\dfrac{1}{2}=>\dfrac{x}{5}=\dfrac{1}{10}=>x.10=5=>x=\dfrac{1}{2}\)
e) \(\dfrac{x+3}{15}=\dfrac{1}{3}=>\left(x+3\right).3=15=>x+3=5=>x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{x}{y}\times\dfrac{3}{4}=\dfrac{5}{6}+\dfrac{1}{3}\)
\(\dfrac{x}{y}\times\dfrac{3}{4}=\dfrac{7}{6}\)
\(\dfrac{x}{y}=\dfrac{7}{6}:\dfrac{3}{4}\)
\(\dfrac{x}{y}=\dfrac{14}{9}\)
b) \(\dfrac{7}{9}:\dfrac{x}{y}=\dfrac{10}{7}-\dfrac{13}{14}\)
\(\dfrac{7}{9}:\dfrac{x}{y}=\dfrac{1}{2}\)
\(\dfrac{x}{y}=\dfrac{7}{9}:\dfrac{1}{2}\)
\(\dfrac{x}{y}=\dfrac{14}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`2/3 x + 5/7 = 3/10`
`2/3 x= 3/10 - 5/7`
`2/3 x=-29/70`
`x = -29/70 : 2/3`
`x=-87/140`
b) `3/4 .x-1/2=3/7`
`3/4 .x=3/7+1/2`
`3/4 .x=13/14`
`x= 13/14 : 3/4`
`x=26/21`
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
+) \(\dfrac{7}{8}\times y=\dfrac{3}{2}+\dfrac{6}{4}=3\)
\(y=3:\dfrac{7}{8}=\dfrac{24}{7}\)
+) \(\dfrac{1}{y}\times\left(\dfrac{2}{5}+\dfrac{1}{5}\right)=\dfrac{10}{3}\)
\(\dfrac{1}{y}=\dfrac{10}{3}:\dfrac{3}{5}=\dfrac{50}{9}\)
\(y=\dfrac{9}{50}\)
\(\dfrac{10}{7}.x=\dfrac{4}{7}\)
\(x=\dfrac{4}{7}:\dfrac{10}{7}\)
\(x=\dfrac{4}{7}.\dfarc{7}{10}\)
\(x=\dfrac{2}{5}\)